PERLINDUNGAN HUKUM NASABAH BANK DALAM HAL PEMBERIAN INFORMASI NASABAH KEPADA PIHAK FINTECH LENDING BERDASARKAN PRINSIP KERAHASIAAN - Galih Raka Siwi, Galih Raka S (Esensi Hukum, 2021)
Bank is a financial institution that collects funds and distributes public funds, in accordance with Article 3 of the Banking Law. Banking institutions have a very important role, especially in moving the economy of a country. The role of banking cannot be separated from the enactment of Law Number 10 of 1998 concerning Banking. In carrying out its functions and duties, banking cannot be separated from customers, be they depositors or borrowing customers. In carrying out its functions, the Bank is bound by several principles, one of which is the principle of confidentiality. The principle of bank secrecy is regulated in Article 4- to Article 47A of the Banking Law. The principle of confidentiality is very important to be maintained by the bank as a financial service provider, this is related to public trust in the banking sector itself. Banks are prohibited from opening data from customers without permission from the BI leadership or if the law says otherwise. Banks are prohibited from disclosing secrets related to financial data or loans from customers to third parties, in this case the fintech lending party. Banks as service providers will certainly comply with the Consumer Protection Law. The purpose of this paper is to identify and understand the principles of banking confidentiality. The method used in this paper is normative juridical, by examining primary and secondary legal materials, especially in terms of legislation.